(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Any critical condition is accompanied by the accumulation of toxic substances in greater or lesser quantities, which causes damage to cell membranes, disruption of intracellular metabolism, uncoupling of oxidation and phosphorylation in mitochondria, and, ultimately, leads to tissue hypoxia. In some cases, intoxication comes to the fore and begins to play a leading role in the pathogenesis of many systemic diseases, obstetric complications, and severe infections. Unfortunately, their prevalence is steadily growing, and mortality is consistently high. In this regard, the development of efferent methods of treatment in critical conditions has always been one of the priority areas in the research activities of many scientists in the Republic of Uzbekistan and abroad.